We need to talk about antisemitism - Fersko, Diana (Seal Press, 2023)
"Rabbi Diana Fersko is used to having difficult conversations with members of her congregation about how the rise is antisemitism is affecting their lives, from the threat of violence to microaggressions and identity denial. In We Need to Talk About Antisemitism, she gives us the tools we need to understand the state of antisemitism today. Unpacking the origins of the most prominent conspiracy theories about the Jewish people, Rabbi Fersko shows how antisemitism enters our public discourse in sometimes obvious but often incredibly subtle ways. Calling on Jews and non-Jews alike, she teaches us how to speak up against hate--and counter it with a message of solidarity and hope."--Dust jacket flap.